2013
DOI: 10.1097/wno.0b013e3182842553
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Traumatic Optic Neuropathy

Abstract: Decreased AD and mean diffusivity in the posterior segment of the optic nerve may serve as a biomarker of axonal damage in patients with TON and merits further investigation as a predictor of initial visual acuity and potential visual recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Also, RD decreased, and interestingly AD decreased, being the most affected metric ( 115 ). Bodanapally et al [2013] ( 115 ) did notice that their results were in disagreement with Yang et al [2011] ( 114 ), leading them to suggest an alternative putative cellular pathology [see also ( 47 , 116 )]. Li and colleagues [2014] ( 117 ) further investigated this issue and looked more closely at the time-since-onset.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, RD decreased, and interestingly AD decreased, being the most affected metric ( 115 ). Bodanapally et al [2013] ( 115 ) did notice that their results were in disagreement with Yang et al [2011] ( 114 ), leading them to suggest an alternative putative cellular pathology [see also ( 47 , 116 )]. Li and colleagues [2014] ( 117 ) further investigated this issue and looked more closely at the time-since-onset.…”
Section: Resultsmentioning
confidence: 99%
“…In the optic nerve, Yang and colleagues [2011] ( 114 ) find a lower FA and higher MD in the affected compared to the unaffected optic nerve. Although not in the same section of the optic nerve, Bodanapally and colleagues [2013] ( 115 ) found that TON patients have a lower MD in the posterior section of the orbital optic nerve compared to both controls and TBI patients, with no FA difference. Also, RD decreased, and interestingly AD decreased, being the most affected metric ( 115 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, axonal swelling in cytotoxic edema and reduction in the extracellular space that occur secondary to cell swelling also restrict water diffusion. 6,7) Thus, AD, RD, and mean diffusivity can be comprehensively determined based on these effects. Regarding the signal change over time, Mac Donald et al 8) reported that AD significantly decreases in the period between 6 h and 4 days after trauma and that it is “pseudo-normalized,” whereas RD increases in 1–4 weeks after the trauma, depending on the degree of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Direct traumatic optic neuropathy (TON) results from anatomical disruption of the optic nerve, whereas indirect TON originates from optic nerve stretch during a head injury. The latter can also occur due to secondary injury to the retinal ganglion cell axons ( 6 , 7 ). Preclinical studies have showed that repeated mild TBI results in loss of the retinal nerve fiber layer and the inner plexiform layer ( 8–10 ).…”
Section: Introductionmentioning
confidence: 99%